Development of Science-V Learning Media on the Water Cycle Sub-Theme at Madrasah Ibtidaiyah - Widhyahrini, Khusna (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Video-based media is currently being developed with the aim of helping students understand learning material, especially science topics. In this research, video media was created using the Power Director application which has been validated in previous research. This research aims to explain the development of video media created using Power Director for the Water Cycle sub-theme at the Madrasah Ibtidaiyah (MI) level. The method used is an effectiveness test to determine the effectiveness of video media on student learning outcomes using the t-test. This research used as subjects fifth grade students at MI Ma'arif Watuagung in Semarang. Based on an analysis of needs in the field, the school requires a learning video media with Power Director. Video media assisted by Power Director that has been created. The t test is used to test the hypothesis. Based on SPSS calculations, it was obtained -9.173 and the increase in student learning outcomes showed 30.43%. This is shown by the pre-test score of 64.78 and post-test score of 76.95. From these data it can be concluded that the Science-V media is effective in improving MI student learning outcomes on the Water Cycle sub-theme.